2011
DOI: 10.3109/14992027.2011.605806
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two bone anchored hearing instruments: BP100 and Ponto Pro

Abstract: 67% of the subjects opted for permanent use of the Ponto Pro, which, compared to the BP100, was rated to have a nicer look, to be easier to operate, and to yield better speech intelligibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Studies have shown increased speech intelligibility and improved subjective patient satisfaction ratings. 7 There is still debate regarding the optimum time for processor loading; a balance between ensuring osseointegration has occurred and minimising the patient's wait to use the bone-anchored hearing system has to be made. There appears to be little difference in the risk of osseointegration failure for those patients loaded at less than 6 weeks or more than 12 weeks, or even at 4 weeks post-operatively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown increased speech intelligibility and improved subjective patient satisfaction ratings. 7 There is still debate regarding the optimum time for processor loading; a balance between ensuring osseointegration has occurred and minimising the patient's wait to use the bone-anchored hearing system has to be made. There appears to be little difference in the risk of osseointegration failure for those patients loaded at less than 6 weeks or more than 12 weeks, or even at 4 weeks post-operatively.…”
Section: Introductionmentioning
confidence: 99%
“…5 Two participants reported no auditory feedback with the BP100. No such comments were made regarding the Ponto Pro.…”
Section: Auditory Feedbackmentioning
confidence: 99%
“…5 The Nordic Co-operation on Disability questionnaire revealed significantly better median ratings for the Ponto Pro than the BP100 in terms of: speech perception, having a conversation with one person in a car, listening to the television or radio, changing the battery, adjusting the control, and the appearance of the device. 5 The Nordic Co-operation on Disability questionnaire revealed significantly better median ratings for the Ponto Pro than the BP100 in terms of: speech perception, having a conversation with one person in a car, listening to the television or radio, changing the battery, adjusting the control, and the appearance of the device.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations